How Novice Entrepreneurs Learn About Digital Marketing Communication Strategies? - Miftahul Rozaq; Sri Hastjarjo; Yulius Slamet (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2021)
This study aims to investigate the process of learning digital communication strategies by novice entrepreneurs who have limited knowledge, information, and access to formal training by learning through observations on social media to develop their business. This study used a qualitative approach with a case study design of six start-up entrepreneurs from micro, small and medium enterprises in Surakarta, Indonesia. In-depth interviews were conducted with six start-up entrepreneurs to study the social media situation in modeling and the meaning of the social media communication strategy being modeled. The results showed that role modeling occurred based on the needs of novice entrepreneurs to learn social media communication strategies. Also, the correct meaning of social media communication strategies is a determining factor that leads to the self-efficacy of novice entrepreneurs to make similar imitation decisions, develop observed strategies, or create new versions of strategies.